2017
DOI: 10.1158/1055-9965.epi-17-0096
|View full text |Cite
|
Sign up to set email alerts
|

Use of Calcium Channel Blockers and Breast Cancer Risk in the Women's Health Initiative

Abstract: Background Use of calcium channel blockers (CCBs) has been associated with increased risk of breast cancer in some, but not all studies. Differences in reported associations from prior studies may be due, in part, to inadequate control of confounding factors. Methods Participants were 28,561 postmenopausal women from the Women’s Health Initiative who reported use of either CCBs or other anti-hypertensive medications (AHM) at baseline; 1,402 incident breast cancer cases were diagnosed during 12 years of follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
0
13
0
1
Order By: Relevance
“…Some authors therefore suggested that CCB are potentially a confounding factor that might explain the increased incidence of breast cancer in SSc observed in some studies (40). However, all these results have recently been questioned by an epidemiological study taking into account confounding factors and involving 28,000 patients (41). The possible pathophysiological relationship between breast cancer and CCB remains unclear, but a hypothetical mechanism might be an impaired functionality of intracellular calcium associated with CCB, particularly in the initiation of the pro-apoptotic signal.…”
Section: Demonstrated Associations With Specific Cancersmentioning
confidence: 99%
“…Some authors therefore suggested that CCB are potentially a confounding factor that might explain the increased incidence of breast cancer in SSc observed in some studies (40). However, all these results have recently been questioned by an epidemiological study taking into account confounding factors and involving 28,000 patients (41). The possible pathophysiological relationship between breast cancer and CCB remains unclear, but a hypothetical mechanism might be an impaired functionality of intracellular calcium associated with CCB, particularly in the initiation of the pro-apoptotic signal.…”
Section: Demonstrated Associations With Specific Cancersmentioning
confidence: 99%
“…In a large cohort study, Raebel et al reported that compared with CCB use for 1 to 2 years, use for 2 to 12 years did not increase the risk of invasive breast cancer among women aged >55 years (HR, 0.86; 95%CI, 0.27‐2.74). Among postmenopausal women participating in the US Women's Health Initiative, a 12‐year follow‐up cohort study by Brasky et al also reported that CCBs do not influence breast cancer risk (HR, 1.06; 95%CI, 0.94‐1.20). Furthermore, the summative evidence from a meta‐analysis of 9 cohort studies did not support a clear association between CCB use and breast cancer risk (pooled HR, 0.99; 95%CI, 0.94‐1.03, I 2 , 35%) …”
Section: Discussionmentioning
confidence: 99%
“…Recently, a controversial issue has been their association with breast cancer risk. Although CCBs can interfere with apoptotic and miRNA‐524‐5p‐BRI3‐Erk pathways in tumor cells, leading to an increased potential for abnormal cell proliferation and tumor migration, some large population‐based studies and meta‐analyses revealed that CCB use does not increase the risk of breast cancer in women . Furthermore, a number of studies found that CCBs exert anti‐inflammatory and antimigratory effects on macrophages via attenuating Ca 2+ entry into macrophages and then downregulating the expression of plasminogen receptors on the macrophage surface .…”
mentioning
confidence: 99%
“…Several epidemiological investigations report that, calcium channel blockers used for the medical therapy of other pathologies are related with a reduced prostate cancer risk ( Debes et al., 2004 ; Rodriguez et al., 2009 ), or at least a significantly tumor aggressiveness reduction ( Poch et al., 2013 ). There is more discrepancy in studies of other cancer types, ranging from significant diminution in breast cancer risk ( Fitzpatrick et al., 1997 ; Taylor et al., 2008 ) to no association between VGCCs blockers and cancer in colorectal, lung and breast tumors ( Michels et al., 1998 ; Boudreau et al., 2008 ; Devore et al., 2015 ; Brasky et al., 2017 ; Bowles et al., 2019 ), including higher lung cancer risk correlated with exposure to calcium channels blockers ( Rotshild et al., 2018 ).…”
Section: Calcium Permeable Channel Modulators and Cancermentioning
confidence: 99%